(untitled) (Research, Society and Development, 2020)
Storytelling is an important teaching-learning tool for children’s development, as it stimulates children’s imagination and promotes social development. This work aims to report the contributions of a storytelling experience about healthy eating carried out in Teresina, Piaui. This is an experience report of actions developed with students from two to three years of age from a municipal nursery located in Teresina. The action developed is part of the "EducaMonte: Approaching health and school" extension project developed by the Multiprofessional Residency in Family and Community Health of the State University of Piauí. From the original story, the retelling of the "John and Mary" narrative of the Grimm brothers was carried out using storytelling techniques and auxiliary resources. The activity was organized in stages: selection of the resources (dramatization), characterization of the characters, construction of the scenario and presentation of the retelling "John and Mary and Healthy Eating" as well as the discussion with the children about the importance of healthy eating. In this way, it is evident that history is an important pedagogical tool and that, although it seems intuitive to do so, it has a theoretical and practical framework to guide its adequate development.